Event analysis of the COVID-19: evidence from the stock markets of twenty highly infected countries - Tanveer, Zubair (Penerbit Universiti Kebangsaan Malaysia, 2021)
The global lockout triggered by coronavirus has made the disease both a health problem and a global economic crisis. Such pandemic-inflicted movement control has adversely affected many facets of life and business. The present study aims to investigate the impact of such an unexpected outbreak on stocks in twenty highly infected countries, including the USA, Brazil, India, Russia, South Africa, Peru, Mexico, Chile, Spain, United Kingdom, Iran, Pakistan, Saudi Arabia, Italy, Turkey, Colombia, Bangladesh, Germany, France, and Argentina. The descriptive statistics and correlation estimates are reported negative returns and high volatility in the selected countries' stock indices during the epidemic. Empirical findings of event study methodology extracted from abnormal returns, average abnormal returns, and cumulative abnormal returns show significant impacts of coronavirus outbreak on the stock markets. The strict lockdown of cities, the closure of borders, the implementation of social distancing rules, the collapse in oil prices, the closure of all business activities, and other health interventions have exacerbated the uncertainty of the situation of the world's stock markets. The governments and stock exchange authorities should rationalize the financial policies and work together to contain such unprecedented events on stock markets because individual policy by each country may cause further challenging situations for the global financial market. Moreover, it is also useful to digitize companies and other similar operations to contain such a type of black swan incident that adversely affects the economies and damages the health system around the world.